Providing mental health first aid in the workplace: a Delphi consensus study. Issue 1 (December 2016) - Bovopoulos, Nataly; Jorm, Anthony; Bond, Kathy; LaMontagne, Anthony; Reavley, Nicola; Kelly, Claire; Kitchener, Betty; Martin, Angela
Abstract Background Mental health problems are common in the workplace, but workers affected by such problems are not always well supported by managers and co-workers. Guidelines exist for the public on how to provide mental health first aid, but not specifically on how to tailor one's approach if the person of concern is a co-worker or employee. A Delphi consensus study was carried out to develop guidelines on additional considerations required when offering mental health first aid in a workplace context. Methods A systematic search of websites, books and journal articles was conducted to develop a questionnaire with 246 items containing actions that someone may use to offer mental health first aid to a co-worker or employee. Three panels of experts from English-speaking countries were recruited (23 consumers, 26 managers and 38 workplace mental health professionals), who independently rated the items over three rounds for inclusion in the guidelines. Results The retention rate of the expert panellists across the three rounds was 61.7 %. Of the 246 items, 201 items were agreed to be important or very important by at least 80 % of panellists. These 201 endorsed items included actions on how to approach and offer support to a co-worker, and additional considerations where the person assisting is a supervisor or manager, or is assisting in crisis situations such as acute distress. Conclusions The guidelines outline strategies for a worker to use when they are concerned about the mental health of a co-worker or employee. They will be used to inform future tailoring of Mental Health First Aid training when it is delivered in workplace settings and could influence organisational policies and procedures.